2022
DOI: 10.21608/ajnsa.2022.113739.1537
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Cellulose "MC" on some physical properties of Nickel Magnesium Ferrite - MC nanocomposite.

Abstract: Ni0.6Mg0.4Fe2O4 ferrite sample was obtained employing the auto combustion flash technique and is overheated for three hours at 700℃. Utilizing the casting procedure, a freestanding magnetic film was created by combining Ni0.6Mg0.4Fe2O4 nanoparticles with methyl cellulose (MC). X-ray Diffraction (XRD), transmission electron microscopy (TEM), and Fourier transition infrared spectroscopy (FTIR) are hired to depict the structural properties of the synthesized samples. All samples' surface morphology was tutored em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
0
1
Order By: Relevance
“…The present work indicated that P21, P16, p53, and TGFβ-1 gene expressions using RT-PCR a good predictor of cancer treatment and inhibition of angiogenesis and was inconsistent with other studies done by other authors [47][48][49][50][51][52][53][54][55]. In the end, the application of photo-and sono-activated phytochemical nanoparticle (nano-curcumin) as in vivo anti-tumor therapy opens up a new way of research in cancer treatment.…”
Section: Discussioncontrasting
confidence: 99%
“…The present work indicated that P21, P16, p53, and TGFβ-1 gene expressions using RT-PCR a good predictor of cancer treatment and inhibition of angiogenesis and was inconsistent with other studies done by other authors [47][48][49][50][51][52][53][54][55]. In the end, the application of photo-and sono-activated phytochemical nanoparticle (nano-curcumin) as in vivo anti-tumor therapy opens up a new way of research in cancer treatment.…”
Section: Discussioncontrasting
confidence: 99%